Application of diffusive gradient in thin films technique (DGT) to measurement of mercury in aquatic systems - Docekalová, H; Divis, P (Talanta, 2005)
The diffusive gradient in thin films (DGT) technique was investigated and used to measure mercury concentration in river water. Mercury ions are covalently bound to amide nitrogen groups of commonly used polyacrylamide, which makes this gel unsuitable as a diffusive medium. In contrast, agarose gel was found as the diffusive gel for mercury measurements. Basic performance tests of agarose DGT verified the applicability of Fick's first law for DGT measurements. Two selective resins, Chelex-100 with iminodiacetic groups and Spheron-Thiol with thiol groups were used. The measured diffusion coefficient in agarose gel was close to that in water. The concentration of mercury in Svitava river measured by DGT with Speron-Thiol resin gel was higher (0.0116 +/- 0.0009mugl(-1)) than those obtained by Chelex-100 (0.0042 +/- 0.0005mugl(-1)). Different capture efficiencies of two adsorbents enable to estimate fractions of mercury bonded in different complexes in the river water. The concentrations of mercury found by DGT both Chelex-100 and Speron-Thiol resin gels are much lower than that measured directly in the river water (0.088 +/- 0.012mugl(-1)). This difference indicates that DGT concerns inorganic ions and labile species only, and that it is not able to include inert organic species and colloids.